Investigating the effects of an oral fructose challenge on hepatic ATP reserves in healthy volunteers: a 31P MRS study - Bawden, Stephen; Stephenson, M.C.; Ciampi, Elisabetta; Hunter, K.; Marciani, Luca; MacDonald, Ian A.; Aithal, Guruprasad P.; Morris, P.G.; Gowland, Penny A. (Elsevier, 2015)
Background: Impaired homeostasis of hepatic ATP has been associated with NAFLD. An intravenous fructose infusion has been shown to be an effective challenge to monitor the depletion and subsequent recovery of hepatic ATP reserves using 31P MRS. Aims: The purpose of this study was to evaluate the effects of an oral rather than intravenous fructose challenge on hepatic ATP reserves in healthy subjects. Methods: Self-reported healthy males were recruited. Following an overnight fast, baseline liver glycogen and lipid levels were measured using Magnetic Resonance Spectroscopy (MRS). Immediately after consuming a 500 ml 75 g fructose drink (1275 kJ) subjects were scanned continuously for 90 min to acquire dynamic 31P MRS measurements of liver ATP reserves. Results: A significant effect on ATP reserves was observed across the time course (P < 0.05). Mean ATP levels reached a minimum at 50 min which was markedly lower than baseline (80 ± 17% baseline, P < 0.05). Subsequently, mean values tended to rise but did not reach statistical significance above minimum. The time to minimum ATP levels across subjects was negatively correlated with BMI (R2 ¼ 0.74, P < 0.005). Rates of ATP recovery were not significantly correlated with BMI or liver fat levels, but were negatively correlated with baseline glycogen levels (R2 ¼ 0.7, P < 0.05). Conclusions: Depletion of ATP reserves can be measured non-invasively following an oral fructose challenge using 31P.